Margo's Got Money Troubles : a novel - Thorpe, Rufi (New York, NY : William Morrow, 2023)
"A bold, laugh-out-loud funny, and heartwarming story about one young woman's attempt to navigate adulthood, new motherhood, and her meager bank account in our increasingly online world-from the PEN/Faulkner finalist and critically acclaimed author of The Knockout Queen"--.
new book 2024 summer.
Keywords: Bildungsromans; Novels; Coming of age fiction; Humorous fiction